Socio-cultural factors and nursing ethical dilemma affect stunting in indonesian children - Elvira La Bula; Fitri Arofiati (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2025)
Background: Stunting is a body condition that occurs due to chronic malnutrition due to the lack of fulfillment of nutritional needs over a long period of time. In Indonesia, it is estimated that almost less than 20% of children are stunted. Purpose: to outline the socio-cultural factors and ethical dilemmas of nursing that contribute to stunting in children in Indonesia. Method: To achieve this goal, the author conducted a systematic review of quantitative research articles that addressed the topic. Article searches were conducted through Google Scholar and ScienceDirect using keywords such as